Emerging Biological Functions of IL-17A: A New Target in Chronic Obstructive Pulmonary Disease? - Liu, Meiling; Wu, Kang; Lin, Jinduan; Xie, Qingqiang; Liu, Yuan; Huang, Yin; Zeng, Jun; Yang, Zhaogang; Wang, Yifan; Dong, Shiyan; Deng, Weiye; Yang, Mingming; et al. (Frontiers in Pharmacology, 2021)
Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory disease that causes high rates of disability and mortality worldwide because of severe progressive and irreversible symptoms. During the period of COPD initiation and progression, the immune system triggers the activation of various immune cells, including Regulatory T cells (Tregs), dendritic cells (DCs) and Th17 cells, and also the release of many different cytokines and chemokines, such as IL-17A and TGF-β. In recent years, studies have focused on the role of IL-17A in chronic inflammation process, which was found to play a highly critical role in facilitating COPD. Specially, IL-17A and its downstream regulators are potential therapeutic targets for COPD. We mainly focused on the possibility of IL-17A signaling pathways that was involved in the progression of COPD; for instance, how IL-17A promotes airway remodeling in COPD? How IL-17A facilitates neutrophil inflammation in COPD? How IL-17A induces the expression of TSLP to promote the progression of COPD? Whether the mature DCs and Tregs participate in this process and how they cooperate with IL-17A to accelerate the development of COPD? And above associated studies could benefit clinical application of therapeutic targets of the disease. Moreover, four novel efficient therapies targeting IL-17A and other molecules for COPD are also concluded, such as Bufei Yishen formula (BYF), a Traditional Chinese Medicine (TCM), and curcumin, a natural polyphenol extracted from the root of Curcuma longa.